Features of mechanical scanning probe lithography on graphene oxide and As(Ge)Se chalcogenide resist - Lytvyn, P.M.; Malyuta, S.V.; Indutnyi, I.Z.; Efremov, A.A.; Slobodyan, O.V.; Min’ko, V.I.; Nazarov, A.N.; Borysov, O.V.; Prokopenko, I.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2018)
Combined mechanical scanning probe lithography (SPL) approach applied for the direct mask-less modification of graphene oxide (GO) flakes and the mask patterns engraving in layers of chalcogenide resist with a nanometer scale resolution has been implemented in this work. The dynamics of mechanical modification of chalcogenide films and multilayer GO flakes deposited from an aqueous suspension were compared. The double-layer As₄₀Se₆₀/As₄Ge₃₀S₆₆ chalcogenide resist developed for mechanical SPL and pattern formation processes has been optimized. The resist with the thickness close to 100 nm provides formation of minimal pattern elements with a size of several tens of nanometers. The SPL approach was realized on the basis of a serial NanoScope IIIa Dimension 3000ᵀᴹ scanning probe microscope, and original software utilities were developed. These mechanical SPL could be intended for the verification of innovative ideas in academic research, laboratory-level device prototyping, and developing the functional prototypes of new devices in bio/nanosensorics, plasmonics, 2D electronics, and other modern technology branches.